Effect of Vitamin D Supplementation on Aorta Diameter of Pregnant Wistar Rats (Rattus norvegicus) - Haryono, Az Zahra Khaiirunnisa; Cahyanti, Ratnasari Dwi; Mundhofir, Farmaditya Eka Putra; Pramono, M.Besari Adi (Universitas Sari Mulia, 2025)
Background: Hypertension is one of the clinical signs of preeclampsia or eclampsia, which is estimated to be seven times higher in developing countries than in developed countries. It can be caused by the differences in nutritional status and nutritional intake, one of which is vitamin D. Vitamin D deficiency (VDD) has a negative impact on pregnancy. It increases the risk of preeclampsia, long-term hypertension, miscarriage, and vascular disorder. Vasoconstriction as the beginning of preeclampsia can be related to the diameter of the aorta which is the largest blood vessel in the human body.Purpose: Determine the effect of vitamin D intake on the aorta diameter of pregnant Wistar rats (Rattus norvegicus).Method: True experimental with post-test only control group design. Research on pregnant Wistar rats (Rattus norvegicus) was divided into control and treatment groups. The treatment group of pregnant Wistar rats was given a standard diet during pregnancy and given a dose of 1000 IU/day (human doses) or 18 IU/day (rat doses) of vitamin D on days 1 to 17. On the 18th day, surgery was performed to take the aorta, and its diameter was measured.Results: The mean aorta diameter of the control group was 1742,04 µm and the treatment group was 1889,30 µm.Conclusion: There is a clinical inclination that the mean aorta diameter of pregnant Wistar rats (Rattus norvegicus) in the treatment group given 18 IU vitamin D is greater than the control group.